Investigation of the connection between triglyceride-glucose (TyG) index and the risk of acute kidney injury in septic patients - a retrospective analysis utilizing the MIMIC-IV database - Pirun Zhang; Wenli Zhang; Yan Han; Tong Yang; Jiayi Zhong; Yun Han; Fang Lai (Renal Failure)
The TyG index serves as a valuable tool for evaluating insulin resistance. An elevated TyG has shown a strong association with the occurrence of acute kidney injury (AKI). Nevertheless, existing literature does not address the relationship between the TyG index and acute kidney injury in patients with sepsis. Sepsis patients were identified from the MIMIC-IV database and categorized into four groups according to quadrilles of their TyG index values. The primary outcome of this study was the incidence of AKI. The relationship between the TyG index and the risk of AKI in septic patients was evaluated using Cox proportional hazards and restricted cubic spline models. Subgroup analyses were conducted to investigate the prognostic value of the TyG index in different subgroups. A total of 2,616 patients with sepsis (57% of whom were male) were included in this study. The incidence of AKI was found to be 78%. Cox proportional hazards analysis revealed a significant correlation between the TyG index and the occurrence of AKI in septic patients. Furthermore, a restricted cubic spline model revealed an approximately linear relationship between a higher TyG index and an elevated risk of AKI in septic patients. The trend of the hazard ratio (HR) remained consistent across various subgroups. These findings emphasize the reliability of the TyG index as an independent predictor for the occurrence of AKI and unfavorable renal outcomes in sepsis patients. Nevertheless, establishing a causal relationship between the two requires demonstration through larger prospective studies.